'There's good and bad': parent perspectives on the influence of mobile touch screen device use on prenatal attachment. Issue 12 (2nd December 2022) - Hood, Rebecca; Zabatiero, Juliana; Silva, Desiree; R. Zubrick, Stephen; Straker, Leon
Abstract: The potential for human–computer interaction to have a substantial impact on adults is well documented. However, its potential importance prior to birth has rarely been reported. Parental use of smartphones and tablet computers could influence the relationship between parent and baby during pregnancy (prenatal attachment) and thus child development. Twenty-seven families were interviewed to explore how parents used these devices during pregnancy, and how device use influenced parents' thoughts, feelings and behaviours towards their baby while in utero. All used devices for a variety of purposes, and all described good levels of prenatal attachment. Parents described both disrupted and enhanced connectedness as a result of device use, and increased parental stress. The findings highlight a new opportunity for how device design and use guidelines could support families to maximise benefits and reduce detriments of device use to optimise prenatal attachment, and thus future parent–child attachment and child development. Practitioner summary: Many parents regularly use smartphones and tablet computers while pregnant. This qualitative study found that how devices were used either enhanced or disrupted feelings of prenatal attachment. Practitioners should be aware of potential beneficial and detrimental impacts of device use during pregnancy given implications for future attachment and child development.